Automatização do método k6 para cálculo da armadura de vigas protendidas - Dias Neto, Francisco Sales (Universidade Federal Rural do Semi-Árido, 2018)
Protension is a technique that is on alert, with a resistance and a structural structure mechanism, which is very important for the control of a work, or slender piece, guaranteeing a force of the same. The modeling of a sizing tool for prestressed beams is of paramount importance and for this, it follows the following steps: implantation of the methodology, obtaining the requested stresses in the beam, assigning the geometry of the section of the beam and inserting the materials that will be used to size the structural element; the need to use such tools, is explained by the savings in time and labor, where the creation of spreadsheets with automated calculation procedures become paramount optimizing the results. With this purpose, the present work aims to use programming principles in order to generate a tool for sizing of prestressed beams. Thus, for the modeling of the tool, the practical process method K6 was used, for the active and passive armature dimensioning of a rectangular section of a beam. Therefore, a spreadsheet was designed to automate and facilitate the calculations to solve problems of prestressing. The spreadsheet determines, with very little initial input data, the proportions of active, passive armor and a number of other results inherent in the design of prestressed beams. It is worth emphasizing that, the spreadsheet presented high precision when solving the example for validation of the method and even if it is easy to use, the same one required by the user is able to interpret the generated data.
Monografia
Keywords: Modelagem; Protensão; Método K6; ENGENHARIAS::ENGENHARIA CIVIL